Degradation of Aniline & Para- Chloroaniline from Water by Adsorption Coupled with Electrochemical Regeneration - Syed muhammad Shahid Hussain; Syed Nadir Hussain; Hafiz Muhammad Anwaar Asghar; Hamed Sattar (Department of Chemical Engineering, Universitas Gadjah Mada, 2023)
Treatment methods for water-containing organics are gaining significant attraction in modern-day research. Amines are an important organic compound class encountered in industrial wastewater streams. The current research paper focuses on studying the adsorption behavior of aniline and parachloro-aniline using a graphite-based adsorbent, namely, Nyex-1000, and the subsequent regeneration of the adsorbent. To determine Nyex-1000's adsorption capacity, several parameters, including time, pH, and concentration, were assessed. Adsorption isotherms, kinetics, and used adsorbent regeneration were also investigated. The adsorption of aniline and parachloro-aniline was found to be quite rapid owing to its non-porous nature. Moreover, the low energy requirement makes the process quite economical due to the high electrical conductivity of the adsorbent. The adsorption data was fitted to Langmuir, Freundlich, Redlich Peterson, Sips, and Toth isotherm models. In aniline’s case, Langmuir and Parachloro-aniline Sips models gave the best fitting with the highest R2 value. A regeneration efficiency of 100% was observed in case of both aniline and parachloro-aniline by passing a charge of 5 and 10 coulombs per gram through the adsorbent bed 10 mm in thickness. Adsorption for parachloro-aniline was found to be 0.88 mg/g, and for aniline was found to be 0.40 mg/g. The reduction in adsorption capacity was minimal after several adsorption and regeneration cycles. This study found that spent adsorbent could be regenerated effectively through electrochemical regeneration.